Landscape regeneration of Paco-Pandacan’s industrial heritage Sites towards Landscape Identity revivification for an integrated sustainable urban renewal - Paderes, Manolo Jr. B.; Villa Juan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Paco and Pandacan (referred in this paper as Paco-Pandacan) are two of the 14 city districts of Manila. This urban landscape has traces of industrial remains which shows the historical background of the area as an industrial hub. Currently decimated, loss of the physical records of this history; ultimately, the significant suppression of the area’s sense of identity could happen. More pressing, further counterproductive plans and “developments” of gray infrastructures continues despite the evident lack of open green spaces which directly threatens the life of the city and the quality of life therein. This implies an urgent need for an integrated sustainable urban renewal of the area by addressing its issue on landscape identity and how that could contribute to the improvement of its existing urban landscape. Following this narrative, this thesis paper seeks to revivify Paco-Pandacan’s landscape identity through landscape regeneration of its industrial heritage sites into open green spaces to revivify its landscape identity towards sustainable urban renewal. Out of three created scenarios, the extensive regeneration scenario is found to be the best through assessment criteria including sustainability and landscape identity revivification parameters. The chosen scenario, integrated to the entire area creates a holistic masterplan that identifies every potential site for regeneration. This and other planning schemes were then concluded to be important in reaching the goal of an integrated sustainable urban renewal of Paco-Pandacan.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Urban renewal -- Paco; Urban renewal -- Pandacan; Historic sites -- Paco; Historic sites -- Pandacan; Urban landscape architecture -- Paco; Urban landscape architecture -- Pandacan